2017
DOI: 10.1016/s2214-109x(17)30248-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of provision of home-based curative health services by public sector health-care providers on neonatal survival: a community-based cluster-randomised trial in rural Pakistan

Abstract: SummaryBackgroundAlthough the effectiveness of community mobilisation and promotive care delivered by community health workers in reducing perinatal and neonatal mortality is well established, evidence in support of home-based neonatal resuscitation and infection management is mixed. We assessed the effectiveness of adding training in neonatal bag and mask resuscitation and oral antibiotic therapy for suspected neonatal infections to a basic preventive and promotive interventions package delivered by public se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 34 publications
0
41
0
Order By: Relevance
“…These findings from UP add to a substantial body of evidence across the developing world suggesting that CHWs can play an important role in safeguarding the health of women and their newborns, 4,6,20,21,[31][32][33] especially those in the poorest parts of society. 22 Their position on the frontlines provides a bridge especially for the rural poor into the formal healthcare system.…”
Section: Discussionmentioning
confidence: 62%
“…These findings from UP add to a substantial body of evidence across the developing world suggesting that CHWs can play an important role in safeguarding the health of women and their newborns, 4,6,20,21,[31][32][33] especially those in the poorest parts of society. 22 Their position on the frontlines provides a bridge especially for the rural poor into the formal healthcare system.…”
Section: Discussionmentioning
confidence: 62%
“…Although not explicitly mentioned by mentors in interviews, a recent systematic review identified workload as a strong contributor to provider burn out and emotional fatigue in LMICs [ 29 ], which undoubtedly effects quality of care. While, training more ANMs and GNMs should remain a long-term goal [ 30 ], a more immediate solution may be thoughtful task shifting within PHCs to less skilled providers including community health workers known as Ashas [ 31 ]. Approximately 10% of neonates require only the initial steps of NR (drying, warming, and stimulating) whereas 3–6% require further intervention including bag-mask ventilation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The integration of evidence-based interventions for implementation by caregivers has long been considered a promising means to improve neonatal survival 11. We demonstrated that, while the idea of integrating interventions, delivering packages by LHWs and engaging caregivers as implementers, has several advantages, it did not translate into improved neonatal survival.…”
Section: Discussionmentioning
confidence: 85%
“…One notable exception was the training and evaluation of traditional birth attendants in rural Zambia in the management of common perinatal conditions that led to significant reductions in newborn morality, especially those in the first 24 hours of life 10. Given that multiple barriers prevent CHWs from accessing a newborn soon after birth,11 efforts are needed to engage pregnant women and families as implementers of newborn interventions 5. The delivery of newborn intervention packages by CHWs for implementation by women and families has potential to sustainably reduce neonatal mortality 4…”
Section: Introductionmentioning
confidence: 99%